Liquid crystal nano-particles, LCNANOP - a SONS II collaborative research project - Goodby, John W.; Bates, Martin; Saez, Isabel M.; Gorecka, Ewa; Kitzerow, Heinz- S.; Guillon, Daniel; Donnio, B.; Serrano, Jose-Luis; Deschenaux, Robert (My University, 2008)
A review. LC-NANOP is an ESF EUROCORES SONS Collaborative Research Project that is addressing an innovative approach to self-organized nanostructures by combination of a variety of org., inorg. and metal scaffolds with the unique self-organization properties of liq. crystals to obtain liq. crystal nano-particles. LC-NANOP is concerned with the synthesis, anal., characterization, modeling and physico-chem. properties of super- and supra-mol. systems which are formed from a nano-particle as a central scaffold, surrounded by a layer of liq. crystal. The self-organization properties of the liq. crystal coating is the driving force leading to the self-assembly of the nano-particles into secondary or tertiary hierarchical structures, with emphasis on the systematic variation of nano-particle size, chirality, shape and functionality. This bottom-up approach to nano-structuring is very powerful as it combines the extraordinary variety of morphologies that liq. crystals present with the combination of functional entities, relevant for chem., biol., optoelectronic, and photonic tasks, etc, to create ordered nano-structures that can be controlled by external stimuli. [on SciFinder(R)]
Keywords: review liq crystal nanoparticle supramol structure self assembly